Clinical characteristics of familial schizophrenia. (14th October 2020) - Liu, Na; Zhou, Hui; Xiong, Xiangyu; Li, Qingwei; Jiang, Xuefeng; Zhao, Jingping; Yang, Xiaoxin; Zhang, Mingyuan; Wang, Xiangqun; Wang, Gang; Yang, Fude; Hu, Jian; et al.
Abstract: Introduction: A family history of psychiatric disorders is one of the strongest risk factors for schizophrenia. The characteristics of patients with a family history of psychiatric disorders have not been systematically evaluated. Methods: This multicenter study (26 centers, 2425 cases) was performed in a Chinese population to examine the sociodemographic and clinical characteristics of schizophrenia patients with a family history of psychotic disorders in comparison with those of patients with sporadic schizophrenia. Results: Nineteen percent of patients had a family history of mental disease. Multiple logistic regression analysis revealed that ≥4 hospitalizations (OR = 1.78, P  = .004), tobacco dependence (OR = 1.48, P  = .006), alcohol dependence (OR = 1.74, P  = .013), and physical illness (OR = 1.89, P  = .001) were independently and significantly associated with a family history of mental disease. Conclusion: Patients with a family history of mental disorders present different demographics and clinical features than patients without a family history of psychiatric disorders.